Pengaruh Model Pembelajaran Anchored Instruction terhadap Hasil Belajar Siswa - Ravinia Sasindua; Meytij Rampe; Marlina Karundeng (Oxygenius Journal Of Chemistry Education, 2020)
This research is an experimental study using the Anchored Instruction learning model. This study aims to determine the effect of the Anchored Instruction learning model on student learning outcomes on the mole concept subject. This research was conducted in class X SMA Negeri 2 Siau Timur with a sample of 40 people. The research design used was a pre-test and randomized two group design. The experimental class uses the Anchored Instruction learning model and the control class uses the conventional learning model. Analysis of the hypothesis test using t-test with a significant level α = 0.05. The test results obtained indicate that the results of tcount> ttable or 2.112> 2.024, thus H0 is rejected and H1 is accepted, this shows that there is a significant difference between the average value of the initial test (posttest) of the experimental group and the control group. So it can be concluded that there is a difference between student learning outcomes using the Anchored Instruction learning model and student learning outcomes using conventional learning models on mole concept subject.